Architektonika : Werke aus der Sammlung der Nationalgalerie - Staatliche Museen zu Berlin, aus der Friedrich Christian Flick Collection im Hamburger Bahnhof. - Knapstein, Gabriele; Felix, Matilda; Hamburger Bahnhof - Museum für Gegenwart (Berlin : Nationalgalerie, 2013)
Architektonika displays works from both the Friedrich Christian Flick Collection im Hamburger Bahnhof and the Nationalgalerie's own collections as well as selected works on loan, which all draw on architecture through different approaches. Sculptural and photographic works, films and paintings illustrate how differently artists have approached the interface between art and architecture since the 1960s.
anlässlich der Ausstellung Architektonika, Nationalgalerie im Hamburger Bahnhof - Museum für Gegenwart - Berlin, 15. September 2011 bis 13. Januar 2013
boek